Control en los procesos de ahorros programados en la Cooperativa de Ahorro y Crédito San Antonio Ltda. Agencia Parroquia La Unión - Jhon José Salvatierra Campos, Jhon José Salvatierra Campos (2019)
Currently, savings and credit cooperatives fulfill a fundamental role in the economy and gradual growth of a country, since they are the main ones in charge of directing the resources obtained by a saver and partner at the same time, through the concession or respective grant of credits to entrepreneurs of the locality. The Cooperativa de Ahorro y Crédito San Antonio Ltda., Is a company dedicated to offer different financial services that can contribute to the consecutive contribution in search of constant development with the purpose of improving in a great proportion the quality of life of the inhabitants in general, and therefore in turn stimulate the virtue of saving in the community, this being the place where this case study was executed with the following subject: CONTROL IN THE SAVINGS PROCESSES PROGRAMMED IN THE SAN ANTONIO LTDA SAVINGS AND CREDIT COOPERATIVE. LA UNIÓN PARISH AGENCY, this work is determined in the research subline of the career named Management of Accounting Information